Prognosis Value of Early Veno Arterial PCO2 Difference in Patients Under Peripheral Veno Arterial Extracorporeal Membrane Oxygenation. Issue 6 (December 2020) - Ellouze, Omar; Nguyen, Maxime; Missaoui, Anis; Berthoud, Vivien; Aho, Serge; Bouchot, Olivier; Guinot, Pierre Grégoire; Bouhemad, Belaid
ABSTRACT: Introduction: Veno arterial membrane oxygenation (VA ECMO) is increasingly used for cardiogenic failure. However, hemodynamic targets for adequate resuscitation remain a challenge. The PCO2 gap and the ratio between PCO2 gap and the arteriovenous difference in oxygen (PCO2  gap/Da–vO2 ) are marker of peripheral hypoperfusion. We hypothesized that the PCO2 gap and the PCO2  gap/Da–vO2 ratio might be useful parameters in VA ECMO patients. Patients and Methods: We conducted an observational prospective study between September 2015 and February 2017. All consecutive patients >18 years of age who had been treated with peripheral VA ECMO for cardiac failure were included. We compared two groups of patients: patients who died of any cause under VA ECMO or in the 72 h following VA ECMO weaning (early death group)—and patients who survived VA ECMO weaning more than 72 h (surviving group). Blood samples were drawn from arterial and venous VA ECMO cannulas at H0, H6, and H24. The ability of PCO2 gap and PCO2  gap/Da–vO2 to discriminate between early mortality and surviving was studied using receiver operating characteristic curves analysis. Results: We included 20 patients in surviving group and 29 in early death group. The PCO2 gap was higher in the early death group at H6 (7.4 mm Hg [5.7–10.1] vs. 5.9 mm Hg [3.8–9.2], P  < 0.01). AUC for PCO2 gap at H6 was 0.76 (0.61–0.92), with a cutoff of 6.2 mm Hg. The PCO2  gap/Da–vO2 was higher in the early death group at H0 (2.1 [1.5–2.6] vs. 1.2 [0.9–2.4], P  < 0.01) and at H6 (2.1 [1.3–2.6] vs. 1.0 [0.8–1.7], P  < 0.01). AUC for PCO2  gap/Da–vO2 at H0 and H6 were 0.79 and 0.73 respectively; the cut-off value was 1.4. Conclusions: Early PCO2 gap and PCO2  gap/Da–vO2 ratio are higher in the early death group in patients under VA ECMO. Abstract : Supplemental Digital Content is available in the text